An Association of Dietary Diversity with the Nutritional Status of Cardiovascular Diseased Patients in the Private Tertiary Care Unit of District Peshawar - Hamayun, Mehreen; Fatima, Taqdees; Ghaffar, Fazia; Zafar, Laila (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES The aim of this study was to analyze the effect of socio-demographic and dietary intake patterns on the nutritional status of cardiovascular disease (CVD) patients and to determine the dietary diversity of the households. METHODOLOGY This cross-sectional study was conducted from May 2018 to June 2018 at the Rehman Medical Institute, Peshawar. Based on written consent, a sample of 250 adult CVD patients was selected through a convenient sampling method. The data was collected through a structured questionnaire containing demographic, anthropometry, biochemical, clinical data, and a dietary record. RESULTS In a sample of 250 patients mean age was 55.41±12.558. On the basis of BMI, almost 52.8% were overweight and 0.8% of the patients were obese. Overweight was the major trend among the patients where this tendency was more common in males (57.5%) as compared to females (41%). Diabetes and hypertension were the major complications among these patients. Daily and per week food frequency and dietary diversity scores showed high intake of meat, milk, saturated fats, high glycemic index fruits, intake of processed foods along with good consumption of vegetables. The regression coefficient of DDI showed whole milk, cream, meat and processed meat as a strong predictor of obesity, overweight and CVD. CONCLUSION The overall dietary diversity of the patients showed a trend toward western dietary patterns with a focus on meat, whole milk, and processed foods. Among the financially stable families of Khyber Pakhtunkhwa, this dietary trend may pose a serious health concern in the context of non -communicable diseases in this region and demand for nutrition education at all levels of the society.